PENGALAMAN IBU PASCA PERSALINAN DAN MENYUSUI DENGAN ASUHAN KEBIDANAN KOMPLEMENTER - Nora Rahmanindar; Evi Zulfiana; Seventina Nurul Hidayah (Jurnal Ilmiah Kebidanan Imelda, 2023)
Complementary and alternative medicine in some midwifery communities has become an important part of midwifery practice. For midwives and women, complementary midwifery services are an alternative choice to reduce medical interventions in postpartum and breastfeeding mothers. Complementary therapy is one of the community's treatment options, especially for postpartum and breastfeeding mothers. The purpose of this study was to determine the experiences of postpartum and breastfeeding mothers with complementary postpartum midwifery care. The research method used is a qualitative research method with a phenomenological design. Data collection was carried out by way of in-depth interviews. The sample of this study were 10 respondents consisting of 5 postpartum and breastfeeding mothers who used complementary postpartum midwifery care as the main informants and 5 husband respondents as triangulation informants using purposive sampling technique. The results of this research are that postpartum and breastfeeding mothers have good experience and are happy with providing complementary postpartum midwifery care, the response of respondents is good, because they can provide alternative treatments that are given to provide solutions that occur during postpartum and breastfeeding mothers.